Preparation of PPSU Hollow Fiber Nanofiltration Membranes for Nanofiltration Application - Sherhan, Bashir Y.; Abbas, Areej D.; Alabdly, Hussein A.; Mohammed, Thamer J.; Alsalhy, Qusay F.; Kidher, Thamera; Fahad, Lamees H.; Ahmed, Hamsa; Melkon, Remonda H. (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
PPSU hollow fiber nanofiltration membranes are prepared by applying two concentrations and various extrusion pressures according to the phase inversion method. Cross-sectional area and outer structures were characterized by using scanning electron microscope (SEM) and atomic force microscopy (AFM). In additional to the pore size distribution, either the mean roughness or the mean pore size of the PPSU hollow fiber surfaces was evaluated by AFM. It was found that the morphology of the PPSU fibers had both sponge-like and finger-like structures through different extrusion pressures and PPSU concentrations. The mean pore size and mean roughness for inner and outer surfaces were seen to be decreased with the increase of extrusion pressure at two different PPSU concentrations. Moreover, the lead ion rejection was significantly improved from 19 to 78 % with increasing the extrusion pressure from 2.5 to 3 bar at 25 wt.% PPSU concentration.